3 x 1 5 3x 8x 1
1、
2 3 2 12、
2 45、
2 2
6 3(x ) 46 、
28、 3 3
22x 15x 2 4x 1 2
(x+1)-2(x-1)=1-3x
29、 47 、
2(x-2)-6(x-1)=3(1-x) 5z 4 77 z9 1239 z
30、
3 x 2 5x 1 3 2y 1 2y 3
31、 48、
2(x 1) 4 23m 13m 1 m 7
32、 49、
15-(8-5x)=7x+(4-3x) 323y212 y41 y
33、 50、
51 、
2(x-2)-3(4x-1)=9(1-x) 72x134x153x210
34、
15-(8-5x)=7x+(4-3x) 2x 3 x 3
35、 52、
2(x-2)+2=x+1 2 1200x = 200022 x
36、 53、
(5y+1)+ (1-y)= (9y+1)+ (1-3y) 100 x 8870 x
37、 54、
7(2x-1)-3(4x-1)=4(3x+2)-1 100 x 88 x 70
38、 55、
180%x 190%x 1
56
解方程计算题专练 来自淘豆网m.daumloan.com转载请标明出处.